2015
DOI: 10.1016/j.ajpath.2014.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Multidrug Transporter in Tumor Endothelial Cells Enhances Antiangiogenic Effects of Low-Dose Metronomic Paclitaxel

Abstract: Tumor angiogenesis plays an important role in tumor progression and metastasis. Tumor endothelial cells (TECs) are a therapeutic target of antiangiogenic chemotherapy that was recently developed and is currently being investigated in the clinic with promising results. Low-dose chemotherapy, which is the long-term administration of relatively low doses of chemotherapeutic agents, has been proposed for targeting tumor angiogenesis in various types of cancers. Although the efficacy of low-dose chemotherapy has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…We purchased 7‐week‐old female nude mice (BALB/c AJcl‐nu/nu) from CLEA Japan and housed them under specific pathogen‐free conditions. To visualize metastases to lungs, we used IVIS Spectrum (Caliper Life Science, Hopkinton, MA), Rluc‐expressing A375SM cells . We injected Rluc‐transfected A375SM (1 × 10 6 cells) subcutaneously into the right flanks of nude mice.…”
Section: Methodsmentioning
confidence: 99%
“…We purchased 7‐week‐old female nude mice (BALB/c AJcl‐nu/nu) from CLEA Japan and housed them under specific pathogen‐free conditions. To visualize metastases to lungs, we used IVIS Spectrum (Caliper Life Science, Hopkinton, MA), Rluc‐expressing A375SM cells . We injected Rluc‐transfected A375SM (1 × 10 6 cells) subcutaneously into the right flanks of nude mice.…”
Section: Methodsmentioning
confidence: 99%
“…The ABC transporter family of proteins is also well characterized for its ability to efflux a wide range of small molecules and drugs. It was also reported that tumor ECs are resistant to low-dose chemotherapy through expression of ABCB1 (33). Therefore, to clarify the mechanism responsible for this differential sensitivity to antiangiogenic drugs, we investigated the expression of mRNA for the ABC drug transporters.…”
Section: Ec-sp Cells Are Resistant To Antiangiogenic Therapymentioning
confidence: 99%
“…The high expression of P-gp in many types of cancer tissues was reported to be correlated with a more aggressive phenotype [3,4,7,11,13,14]. In addition to being a drug transporter, in vitro studies also demonstrated additional functions of P-gp, such as for apoptosis and proliferation [5], cancer stem cells [5,17,18], angiogenesis [15,16], cell invasion and metastasis [19,20,21,22], which are critical for cancer initiation and progression. Previous studies have suggested that P-gp exerts its tumor-promoting function through protein–protein interaction [7,20,23].…”
Section: Discussionmentioning
confidence: 99%
“…Upregulated P-gp expression in cancer tissues is usually associated with a more malignant phenotype and poor clinical outcome for cancer patients [3,4,7,11,13,14]. Moreover, P-gp activity was associated with angiogenesis [15,16], cancer stem cells [5,17,18], cell migration and invasion [7,19,20,21,22], which are essential for carcinogenesis and cancer progression. These findings suggest that upregulated P-gp may confer enhanced cell invasion ability in drug-resistant cells.…”
Section: Introductionmentioning
confidence: 99%